Cognitive Assessment Concern and Learning Outcomes of Selected Under-Graduate Students At MLRIT-Hyderabad - Reddy, Kolanu Kiran; Reddy, P. Bhaskara (Transactions on Engineering and Computing Sciences, 2015)
This study investigated the level of Cognitive Assessment Concern of selected undergraduate students. It also sought to find out whether CAC of students vary by ability (performance) levels and sex. A total of 246 purposively selected undergraduate students completed the 32-items Cognitive Assessment Concern Scale. Data were analyzed using contingency table and t-assessment. Results showed that students CAC was generally low. It was also discovered that CAC negatively affects performance levels; the higher the level of students' CAC, the lower the level of students learning outcome and vice-versa. However, sex differences do not lead to Corresponding differences in CAC and performance levels.